Determinants of Financial Management Accountability and Transparency and its Impact on Public Trust: Study on Villages in Banyudono Subdistrict, Boyolali Regency (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to examine the effect of financial report presentation, financial report accessibility, and monitoring mechanisms on financial management accountability and financial management transparency, as well as to examine their impact on public trust. This quantitative research uses primary data obtained by distributing questionnaires to 90 selected respondents who are village heads, village secretaries, finance heads, planning heads, and two members of the Village Consultative Body in Banyudono District, Boyolali Regency. Data analysis used variant-based structural equation modeling. The results showed that financial management accountability was only influenced by the presentation of financial reports, while financial management transparency was influenced by the presentation of financial reports, and monitoring mechanisms. Public trust is only influenced by financial management transparency. These results indicate that the more transparent the government is in terms of financial management and access to important information, the more public trust will increase.